Management of myocardial infarction in pregnant women: A narrative review of recommendations - Tomczak, Ernest; Matewski, Karol; Gawinski, Łukasz; Kozłowski, Remigiusz (Nursing Problems / Problemy Pielęgniarstwa, 2025)
Pregnancy-associated myocardial infarction (PAMI) is extremely rare clinical condition, and its etiology differs from acute coronary syndromes in general population. Most common cause of PAMI is the spontaneous dissection of coronary arteries, caused by metabolic and hormonal changes associated with pregnancy. Currently existing guidelines of cardiac societies do not adequately address this problem. In this review article, a summary of seventeen publicly available articles in the PubMed database was presented, and its purpose was to assist clinicians in appropriate decision-making on the management, treatment, and follow-up care of patients. PAMI requires a cooperation of a multidisciplinary team of cardiologists, anesthesiologists, gynecologists, midwives, and nurses, taking into account gestational age, clinical condition of the mother and fetus, the effect of ionizing radiation, and antiplatelet and anesthetic drugs.